The Aspergillus fumigatus cell wall integrity signaling pathway: drug target, compensatory pathways, and virulence - Valiante, Vito; Macheleidt, Juliane; Föge, Martin; Brakhage, Axel A. (Frontiers in Microbiology, 2015)
Aspergillus fumigatus is the most important airborne fungal pathogen, causing severe infections with invasive growth in immunocompromised patients. The fungal cell wall prevents the cell from lysing and protects the fungus against environmental stress conditions. Because it is absent in humans and because of its essentiality, the fungal cell wall is a promising target for antifungal drugs. Nowadays, compounds acting on the cell wall, i.e. echinocandin derivatives, are used to treat A. fumigatus infections. However, studies demonstrating the clinical effectiveness of echinocandins in comparison with antifungals currently recommended for first-line treatment of invasive aspergillosis are still lacking. Therefore, it is important to elucidate cell wall biosynthesis pathways and their signal transduction cascades, which potentially compensate the inhibition caused by cell wall- perturbing compounds. Like in other fungi, the central core of the cell wall integrity (CWI) signalling pathway in A. fumigatus is composed of three mitogen activated protein kinases. Deletion of these genes resulted in severely enhanced sensitivity of the mutants against cell wall-disturbing compounds and in drastic alterations of the fungal morphology. Additionally, several cross-talk interactions between the CWI pathways and other signalling pathways are emerging, raising the question about their role in the cell wall compensatory mechanisms. In this review we focused on recent advances in understanding the CWI signalling pathway in A. fumigatus and its role during drug stress response and virulence.